World Bank Group Publications Editorial Style Guide 2020 - World Bank Group (World Bank, Washington, DC, 2020)
The World Bank Group Publications Editorial Style Guide is an essential reference for manuscript editors (substantive and mechanical editors), proofreaders, and production editors. It is a supplement to other editorial references, in particular, The Chicago Manual of Style (annual subscription available online), 17th edition, and Merriam-Webster’s Collegiate Dictionary, 11th edition. It focuses on issues specific to the World Bank/International Bank for Reconstruction and Development (IBRD) or for which Chicago provides multiple options. The professional recommendations made in the guide are designed to meet the following objectives: • To ensure that every publication achieves a standard of professionalism appropriate for the World Bank and on par with the publications of similar organizations, • To ensure stylistic consistency, primarily within individual publications and secondarily across all World Bank publications, • To increase efficiency by eliminating the need to repeatedly address the same stylistic details for every publication.